Connectivity and discontinuity in social work practice: Challenges and opportunities of the implementation of an e-social work system in Romania - Anca Mihai; Georgiana-Cristina Rentea; Daniela Gaba; Florin Lazăr; Shari Munch (Journal of Comparative Research in Anthropology and Sociology, 2016)
To increase the efficiency of the social work system in Romania, “investments in improving the current IT system in order to build an efficient electronic social work system” (Romanian Government, 2015b, 85) and the “development of a modern payment system” (Romanian Government, 2015b, 85) are key-points in the National Strategy concerning Social Inclusion and Poverty Reduction for the period 2015-2020. Among other utilisations, the e-social work system is meant to be used by potential clients when submitting a request to benefit of means-tested measures. The current level of digitalisation of the Romanian society, particularly among vulnerable groups, leaves room for constructive debate regarding the feasibility and the potential challenges of such a project. The purpose of this paper is to identify the challenges posed to social workers’ daily practice by the introduction of digitalisation in the work place, as well as its potential effects on the social worker-client professional relationship. We discuss based on the national strategies and data provided by the Digital Economy and Society Index (DESI) (connectivity infrastructure and quality, digital skills of human capital, use of internet by citizens, integration and digital technology, and digital public services). We identify gaps between the aims and the proposed solutions concerning the e-social work system. Our study contributes to understanding the potential changes in social workers’ traditional roles brought forth by the implementation of a digitized social work system.